Numerical Analysis of the Drag Coefficient on Energy-Efficient Vehicle Prototypes - Hendry Sakke Tira; Muhammad Agus Muliawan; Syahrul Syahrul (ROTASI, 2023)
The focus of this investigation is to determine the drag coefficient on the prototype vehicle and also the pressure profile on the entire body of the prototype. The study was carried out on a prototype vehicle that would compete at Shell Eco-Marathon Asia-Pacific and Middle East 2023. The test was performed on an energy-efficient vehicle prototype built by the Mandalika Desantara Team, a team of mechanical engineering students at Mataram University. To accomplish this, a CFD approach simulation was performed using the Ansys 2023 R2 simulation software - fluent flow with a comparison of the drag coefficient and average pressure and wind speed of 30 km/h. According to the simulation results, the average drag coefficient value on the prototype design is 0.194. The highest average pressure can be detected on the front of the vehicle, where that part has a maximum pressure of 101374 Pa. While the airflow over the prototype body has the highest average speed of around 10 m/s. Based on these results, the prototype vehicle design still needs to be improved in order to compete in similar competitions.